2021
DOI: 10.1002/aoc.6487
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of new palladium complex immobilized on (chitosan)/PoPD biopolymer and its catalytic application in Suzuki cross‐coupling reaction

Abstract: The present work reports the design, synthesis, and characterization of palladium complex immobilized on chitosan/poly(o-phenylenediamine) (CS-PoPD-Pd) for the catalytic application in the Suzuki-Miyaura C C cross-coupling reaction through a nontoxic, inexpensive, eco-friendly, and practical method. Fourier-transform-infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), elemental mapping, X-ray diffraction (XRD), and inductively coupled plasma-optical em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In 2022, Seyedi et al described the preparation of a palladium catalyst deposited on a poly(o-phenylenediamine)-grafted chitosan in a two-step procedure: first, an aqueous solution of chitosan was treated with o-phenylenediamine for 1 h at room temperature in the presence of sulfuric acid, in order to allow the in situ polymerization of o-phenylenediamine, giving the grafted biopolymer (indicated as CS-PoPD); the resulting CS-PoPD was then added to a solution of PdCl 2 in methanol, and the resulting suspension was stirred for 24 h at room temperature to give the final supported catalyst (named CS-PoPD-Pd) [110]. In particular, the immobilization of palladium occurred in the form of Pd(II) complexes, as confirmed by the XRD pattern: no new diffraction peaks appeared after the treatment of the CS-PoPD support with PdCl 2 ; moreover, SEM images showed that the o-phenylenediamine polymerization led to a flake-like structure.…”
Section: Cross-coupling Reactions Promoted By Palladium Catalysts Sup...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Seyedi et al described the preparation of a palladium catalyst deposited on a poly(o-phenylenediamine)-grafted chitosan in a two-step procedure: first, an aqueous solution of chitosan was treated with o-phenylenediamine for 1 h at room temperature in the presence of sulfuric acid, in order to allow the in situ polymerization of o-phenylenediamine, giving the grafted biopolymer (indicated as CS-PoPD); the resulting CS-PoPD was then added to a solution of PdCl 2 in methanol, and the resulting suspension was stirred for 24 h at room temperature to give the final supported catalyst (named CS-PoPD-Pd) [110]. In particular, the immobilization of palladium occurred in the form of Pd(II) complexes, as confirmed by the XRD pattern: no new diffraction peaks appeared after the treatment of the CS-PoPD support with PdCl 2 ; moreover, SEM images showed that the o-phenylenediamine polymerization led to a flake-like structure.…”
Section: Cross-coupling Reactions Promoted By Palladium Catalysts Sup...mentioning
confidence: 99%
“…Scheme 35. Suzuki-Miyaura coupling of aryl halides with phenyl boronic acid promoted by a palladium catalyst deposited on a poly(o-phenylenediamine)-grafted chitosan (CS-PoPD-Pd), reported in 2022 by Seyedi et al [110].…”
Section: Cross-coupling Reactions Promoted By Palladium Catalysts Sup...mentioning
confidence: 99%
“…Therefore, to obtain a good yield of the desired cross-coupled product, the reaction was studied by varying different reaction parameters. Literature reports suggest that the solvent system plays a vital role in the SMCC reaction. ,, Hence using the same amount of substrate, catalyst, and base, the reaction was performed in different organic solvents at room temperature. The solvent optimization graph depicted in Figure S7 suggested that CH 3 OH was more suitable in comparison to other solvents like EtOH, CH 3 CN, and isopropanol for this particular reaction under these conditions.…”
Section: Catalytic Studymentioning
confidence: 99%